Unveiling phonons in a molecular qubit with four-dimensional inelastic neutron scattering and density functional theory - E. Garlatti (Nature Portfolio, 2020)
Molecular nanomagnets have potential applications for storing both classical and quantum information, with benefit of the high scalability of chemical synthesis. Here the authors use state-of-the-art experimental and theoretical methods to investigate phonons in a molecular qubit candidate.